Dorobek publikacyjny pracowników Instytutu Filologii Polskiej Uniwersytetu Zielonogórskiego na łamach rocznika w latach 2015-2024 (numery 1-10) = The Employees of the Institute of Polish Philology of Zielona Góra University publication output in the 2015-2024 yearbook issues (issues 1-10) - Majkowska, Michalina; Sztyber, Radosław (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The register below covers information on materials published within columns of "Filologia Polska. Roczniki Naukowe Uniwersytetu Zielonogórskiego" within 2015-2024 authored by the employees of the Institute of Polish Philology of Zielona Góra University. This bibliography was prepared on the occasion of the tenth anniversary of the yearbook?s existence. Many authors have already parted ways with the university, which is why the principle of taking into account the affiliation according to the time of publication of the text was used for archiving reasons. Records also represent contribution of scholars, working in Zielona Góra Institute, into the yearbook progress.
Keywords: bibliografia; Uniwersytet Zielonogórski - Instytut Filologii Polskiej; "Filologia Polska. Roczniki Naukowe Uniwersytetu Zielonogórskiego"